2021
DOI: 10.1002/zaac.202100219
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Thermal Transformations of Methylammonium Tungstate

Abstract: Methylammonium paradodecatungstate, (CH3NH3)10[H2W12O42] ⋅ nH2O, was prepared by the reaction of WO3 or H2WO4 in aqueous methylamine, followed by drying. The [H2W12O42]10− anion consists of two HW3O13 groups containing three edge‐sharing WO6 octahedra and two W3O14 groups having two edge‐sharing connections. On drying the produced material at 70 °C, some lattice water was released, but this did not affect the [H2W12O42]10− structure, although there was a decrease in the unit cell volume. By adding water, the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…In addition to the appearance of H 2 O and CH 3 NH 2 , the degradation and oxidized species of methylammonium such as NH 3 , CO, N 2 , NO, CO 2 , and N 2 O were observed, indicating that a redox reaction between methylammonium and Mo has occurred under inert gas flow. Similar degradation and oxidation reactions of methylamine in methylammonium paradodecatungstate and vanadate under inert gas flow have been observed. , …”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…In addition to the appearance of H 2 O and CH 3 NH 2 , the degradation and oxidized species of methylammonium such as NH 3 , CO, N 2 , NO, CO 2 , and N 2 O were observed, indicating that a redox reaction between methylammonium and Mo has occurred under inert gas flow. Similar degradation and oxidation reactions of methylamine in methylammonium paradodecatungstate and vanadate under inert gas flow have been observed. , …”
Section: Resultssupporting
confidence: 70%
“…Similar degradation and oxidation reactions of methylamine in methylammonium paradodecatungstate and vanadate under inert gas flow have been observed. 22,23 In situ heating powder XRD experiments confirmed that structure transformation occurred during heating (Figure S9). The heating of (CH 3 NH 3 ) 2 [MoO 4 ] (Figure S9a Effect of Countercations on the Polyoxomolybdate Structure Produced by Solid-State Heating.…”
Section: Polyoxomolybdates Isolated From Aqueous Solutions Of Differe...mentioning
confidence: 89%
See 1 more Smart Citation
“…Paratungstate-B is the dominant species in aqueous tungstate solution in a wide pH range and is isolable in the solid state. , The fact that octatungstate instead of paratungstate-B is formed in the presence of {Cp*Ir} 2+ indicates a structure-directing property of {Cp*Ir} 2+ . To test this hypothesis, we carried out a reaction between [(Cp*IrCl) 2 (μ-Cl) 2 ] and methylammonium paratungstate-B (CH 3 NH 3 ) 10 [H 2 W 12 O 42 ]which has a high solubility in wateras the tungsten source. The reaction produced an anionic Cp*Ir–octatungstate complex containing methylamine ligands [(Cp*Ir) 2 {Cp*Ir­(NH 2 CH 3 )} 2 H 2 W 8 O 30 ] 2– ( 4a ) isolated as a methylammonium salt ( 4 ); 4a was also produced by adjusting the pH of a 1:2 [(Cp*IrCl) 2 (μ-Cl) 2 ]/Na 2 WO 4 mixture to 7.5–8.0 by the addition of aqueous methylamine solution from which it crystallized as Na­[(Cp*Ir) 2 (μ-OH) 3 ]­[(Cp*Ir) 2 {Cp*Ir­(NH 2 CH 3 )} 2 H 2 W 8 O 30 ] ( 4′ ).…”
Section: Resultsmentioning
confidence: 99%
“…Structural analyses of polyoxometalates have mostly relied on X-ray or neutron diffraction to establish the solid-state structures of compounds that can be isolated and purified, complemented by spectroscopic tools such as multinuclear solution NMR, Raman, and X-ray spectroscopies. , An illustrative example is ammonium paratungstate (APT), [NH 4 ] 10 [H 2 W 12 O 42 ]­(H 2 O) x , which is the prototypical precursor to tungsten-derived materials, including W oxides, W alloys, and W-based catalysts . APT is poorly soluble in water and dissolves predominantly through conversion of the [H 2 W 12 O 42 ] 10– anion (paratungstate B) into the [W 7 O 24 ] 6– anion (paratungstate A), followed by aqueous phase speciation that depends on the pH, temperature, and nature of cations. , Solution 183 W NMR spectroscopy has long been recognized as a powerful tool for analyzing dissolved polyoxotungstates due to the sensitivity of 183 W chemical shifts to local structures. For instance, for APT and related tungstates, it has been used to establish ion binding sites and the influence of pH and temperature on aqueous speciation .…”
mentioning
confidence: 99%